Monitoring plasmon coupling and SERS enhancement through in situ nanoparticle spacing modulation - Velleman,L; Scarabelli,L; Sikdar,D; Kornyshev,AA; Liz-Marzan,LM; Edel,JB (Faraday Discussions, 2017)
Self-assembled nanoparticle (NP) arrays at liquid interfaces provide a unique optical response which has opened the door to new tuneable metamaterials and for sensing and optical applications. NPs can spontaneously assemble at the liquid-liquid interface, forming an ordered, self-healing, low-defect 2D film. The close proximity of the NPs at the interface results in collective plasmonic modes with a spectral response dependent on the distance between the NPs and induces large field enhancements within the gaps. In this study, we assembled spherical and rod-shaped gold NPs with the aim of improving our understanding of NP assembly processes at liquid interfaces, working towards finely controlling their structure and producing tailored optical and enhanced Raman signals. We systematically tuned the assembly and spacing between NPs through increasing or decreasing the degree of electrostatic screening between NPs with the addition of electrolyte or pH adjustment. The in situ modulation of nanoparticle positioning on the same sample allowed us to monitor plasmon coupling and the resulting SERS enhancement processes in real time, with sub-nm precision.